Peningkatan hasil belajar dan keaktifan siswa melalui media poster pada materi permasalahan lingkungan sekitar di kelas iv min 3 malang - Aghfar, M.Sambuaga (Maliki Interdisciplinary Journal, 2025)
This study aims to improve learning outcomes and student engagement of 4th-grade students at MIN 3 Malang through the use of poster media on the topic of "Environmental Issues in the Surroundings." The research method applied was Classroom Action Research (CAR), conducted in two cycles, including planning, action, observation, and reflection stages. The results showed that poster media effectively increased student participation in discussions, learning interest, and understanding of the material. The average student score rose from 60 (pre-action) to 75.6 in the first cycle and 82.3 in the second cycle. Learning mastery improved from 29.4% to 88.2%. Thus, the use of poster media proved to be effective in enhancing the quality of science-social learning and is highly recommended for use in contextual learning at the elementary level.